Prasangka terhadap Gerakan Hizbul Wathan Muhammadiyah: Antara Pan-Islam dan Nasionalisme Pemuda di Hindia Belanda, 1918-1942 - Safitri, Gita (Universitas Muhammadiyah Yogyakarta, 2025)
The Dutch East Indies Government's prejudice of the rise of Islamic unity from the indigenous people who could defect to oppose the government made a number of native organizations' activities closely monitored. One of them happened to the Muhammadiyah Scouting organization which was suspected of having a pan-Islamic direction which in the future would have the potential to oppose the government. This phenomenon is based on the flourishing of various scouting organizations in the Dutch East Indies and then the background of the events of nationalism and unity. For this reason, this research will analyze the extent of the orientation of the Muhammadiyah scouting movement during the colonial period in the period 1918-1942. In addition, how was the government prejudiced against Muhammadiyah's scouting activities? This research uses a social approach based on the historical method. The sources used in this research include the archives of the colonial government and Muhammadiyah Scouting. The results of this study show that the Muhammadiyah scouting movement, in this case Hizbul Wathan, has an orientation to educate Muhammadiyah youth, but at the same time equipping them with Islamic teaching which is an important difference compared to other scouting movements. The activities carried out by Hizbul Wathan did not show pan-Islamic activities or tendencies towards rebellion despite the government's strict supervision. However, the influence of other youth organizations that consolidated their power made the government wary and took a number of actions to ban scouting activities including Hizbul Wathan activities. The findings of this research contribute to filling the space in the study of Muhammadiyah history in the field of youth and are expected to arouse the spirit of nationalism and nationalism through the scouting movement among Indonesian youth